Accuracy of Magnetic Resonance Imaging in Diagnosis of Anterior Cruciate Ligament and Meniscus Tear: An Observational Study - Sushil Thapa; Sunil Panta; Aarati Adhikari; Hari Prasad Upadhyay; Sarik Kumar Shrestha (Journal of Nepal Medical Association)
Introduction: Magnetic resonance imaging is used for the diagnosis of anterior cruciate ligament and meniscus tears but its value in the diagnosis of these pathologies is limited. This study aims to evaluate the diagnostic value of magnetic resonance imaging in diagnosing anterior cruciate ligament and meniscus tears.